Determinants of Dengue Hemorrhagic Fever Deaths: A Hospital-Based Cross-Sectional Study - Mailiana, Rizki; Fauzi, Lukman (Universitas Negeri Semarang, 2024)
Background: The increase in the dengue mortality rate in Indonesia and its risk factors which must be addressed immediately. Brebes Hospital, a hospital that is the primary referral for health centers and clinics in Brebes Regency, has a dengue mortality rate (Case Fatality Rate) of 7.88%, contributing to the first death rate in Brebes Regency. Data related to dengue deaths, such as comorbidities and hematocrit levels in dengue patients, were unavailable at the provincial and Brebes district levels, especially at Brebes Hospital. This study aims to determine the determinants of dengue death in inpatients at Brebes Hospital. Methods: This cross-sectional study used medical record data of dengue inpatients from September 2021 to August 2022, with as many as 138 respondents using a simple random sampling technique. The research instrument is an observation sheet, including age, gender, incidence of thrombocytopenia, hypotension, hematocrit levels, hemoglobin levels, diabetes mellitus status, hypertension status, comorbidities, and LOS. The data were analyzed in univariate, bivariate with the chi-square test, and multivariate with a logistic regression test. Results: The bivariate analysis results showed that the variables of hypertension status, DM status, thrombocytopenia, hematocrit levels, and the presence of comorbid diseases were associated with dengue mortality (p<0.01). Multivariate analysis showed that after controlling for other variables, the risk of comorbid diseases was significant 27.54 times (p-value <0.001; AOR= 27.54; 95% CI= 7.21-105.07), and hematocrit levels were at risk of 4.96 times increasing dengue mortality (p-value = 0.005; AOR= 4.69; 95% CI= 1.59-13.83). Conclusion: Hematocrit levels and the presence of comorbid diseases are critical determinants of dengue case mortality. The central comorbid diseases are hypertension, diabetes, and stroke. These two factors must be the primary concern of the clinicians in charge of patients in anticipation of an emergency.